The integration of behavioral health consultants within a state-wide psychiatry consultation program: a community case study - Tengelitsch, Elizabeth; Hughes-Krieger, Erin; LePlatte, Dayna; Shaw-Johnston, Samantha; Marcus, Sheila (Frontiers in Psychiatry, 2023)
This paper describes the integration and role of masters-prepared behavioral health consultants (BHCs) within a state-wide psychiatry consultation program for children, adolescents, and perinatal women. Data from the Michigan Clinical Consultation and Care (MC3) program are reviewed, with attention to the role that BHCs play in the consultation process, integrated care, screening, and their dual roles with Community Mental Health Services Programs (CMHSPs) in Michigan. Approximately 82% of MC3 services are provided by the BHCs and involve resources or integrated care. BHCs play a role in managing provider consultations and connecting patients and providers to resources in the MC3 program.